Clinical Feasibility Trial for Transtracheal Stimulation of Vocal Fold Closure in Sensate Human Subjects. (2nd September 2014) - Hahn, Elizabeth C.; Hadley, Aaron; Tyler, Dustin J.; Maronian, Nicole
Abstract : Objectives: (1) Apply transtracheal stimulation (TTS) of the recurrent laryngeal nerve (RLN) for vocal fold closure (VFC) in sensate humans. (2) Characterize tracheal sensory response to electrical stimuli. Methods: Patients with chronic tracheostomies were selected for a "first‐in‐man" clinical device trial to stimulate the RLN through tracheal tissue for VFC. Etiologies of trach dependence varied, but all subjects had normal laryngeal sensation, vocal cord mobility, and RLN function. Devices were introduced through subjects' ostomies, and electrodes were subsequently deployed for tracheal contact. Videoendoscopy recorded responses to square wave pulse trains of varying pulse amplitude (PA) and pulse width (PW; 0.5 mA‐5 mA and 60 us‐500 us, respectively). Subjects were surveyed for sensory changes, discomfort, and pain. Results: TTS of the RLN successfully elicited VFC in all subjects. The PA threshold for closure (ThPA; at PW = 200 us) ranged from 1.5 mA to 3.5 mA unilaterally, and 1.0 mA to 2.5 mA bilaterally for all subjects except 1 outlier with thresholds of 0.9 mA and 1.2 mA unilaterally, and 0.7 mA bilaterally. PW thresholds (ThPW) ranged from 100 us to 300 us for all subjects (PA = 0.75 × ThPA). All subjects denied pain, but 3 described mild incremental "tingling" that initiated cough or swallow responses only at suprathreshold levels. Conclusions: TTS initiated arytenoid medialization for VFC in all subjects without pain or significant discomfort. This study presents a novel technique for noninvasive restoration of VFC in humans. Further trials will determine full clinical utility of this device component, individually and in conjunction with components targeting swallow detection and laryngeal elevation for coordinated airway protection.